Dynamic Capital Mobility in Pacific Basin Developing Countries : Estimation and Policy Implications - Faruqee, Hamid (IMF Working Papers; Working Paper, 1991)
This paper estimates empirically the changing degree of capital mobility in several Pacific Basin countries that have pursued financial liberalization in recent years. Tracing the impact of the liberalization process on the capital account, the paper also examines the implications for monetary policy operating in this changing economic environment. Empirical estimates support an overall finding of increased capital mobility in the region over the past decade. However, country experiences, with the exception of Singapore, have been more episodic--oscillating between periods of high and low financial openness--rather than uniform in regards to changing capital mobility.